Multi‐Functional Liposome: A Powerful Theranostic Nano‐Platform Enhancing Photodynamic Therapy. Issue 16 (3rd June 2021) - Cheng, Xiamin; Gao, Jing; Ding, Yang; Lu, Yao; Wei, Qiancheng; Cui, Dezhi; Fan, Jiali; Li, Xiaoman; Zhu, Ershu; Lu, Yongna; Wu, Qiong; Li, Lin; et al.
Abstract: Although photodynamic therapy (PDT) has promising advantages in almost non‐invasion, low drug resistance, and low dark toxicity, it still suffers from limitations in the lipophilic nature of most photosensitizers (PSs), short half‐life of PS in plasma, poor tissue penetration, and low tumor specificity. To overcome these limitations and enhance PDT, liposomes, as excellent multi‐functional nano‐carriers for drug delivery, have been extensively studied in multi‐functional theranostics, including liposomal PS, targeted drug delivery, controllable drug release, image‐guided therapy, and combined therapy. This review provides researchers with a useful reference in liposome‐based drug delivery. Abstract : Liposomes with high capacity for photosensitizers (PSs), other drugs and imaging agents in hydrophobic bilayer and hydrophilic aqueous core make them capable of executing multi‐functions in disease diagnosis and therapy to enhance photodynamic therapy. The flexibility of surface modification and components of liposome possess the advantages in targeted drug delivery and release.